KERUKUNAN INTERN UMAT BERAGAMA DI KOTA GERBANG SALAM (Melacak Peran Forum Komunikasi ORMAS Islam [FOKUS] Pamekasan) - Nor Hasan (Research Institute and Community Engagement of IAIN MADURA, 2015)
Creating the harmony life in both intern and extern the members of religious community in pluralism is not an easy way. It needs process, as well as social, education, economic, politic especially ideology from each different member of religious. Therefore, it needs serious attention and skill from all sectors: government, public figure and society both individual and group. Forum Komunikasi ORMAS Islam (FOKUS) Pamekasan as the coordinator of silat al-rahim of some ORMAS in Pamekasan commits to realize the harmony life among members of society. Through social activity done, FOKUS has given contribution in realizing the harmony life among members of religious.Copyright (c) by NUANSADOI: 10.19105/nuansa.v12i2.776